Comprehensive Genomic Profiling Reveals the Mutational Spectrum and Clinical Significance of BRCA1/2 and Other Cancer-Susceptibility Genes in Breast Cancer Patients from Southern Tunisia - Nihel Ammous-Boukhris; Rania Abdelmaksoud-Dammak; Wala Ben Kridis; Dorra Ben-Ayed-Guerfali; Souhir Guidara; Ameni Feki; Hassen Kamoun; Afef Khanfir; Jamel Daoud; Gérard-Hubert Lizard; Ali Gargouri; Raja Mokdad-Gargouri (Cancers, 2026)
Background/Objectives: This study aims to investigate the mutational spectrum of BRCA1 and BRCA2 genes in a cohort of breast cancer (BC) patients from southern Tunisia, and to evaluate their clinical and prognostic significance. Additionally, this study explores the contribution of other cancer predisposition genes and the prevalence of variants of uncertain significance (VUS). Results: Among the 165 patients included, pathogenic or likely pathogenic variants (P/LPVs) in BRCA1/BRCA2 were identified in 19 cases (11.51%), including 8 in BRCA1 and 11 in BRCA2. The presence of BRCA P/LPVs associated with young patients (p = 0.006) and those with TNBC (p = 0.036). Beyond BRCA1/2, PV/LPVs were detected in other cancer-related genes, including TP53 (n = 3), CHEK2, RAD50 (n = 2 cases each), and MUTYH, BARD1, and BRIP1 (one case each). Furthermore, 56 VUS were identified; among them, 7 were prioritized based on in silico predictive analyses, suggesting a potential deleterious effect. However, these VUS should not be used for clinical decision-making without additional evidence from functional and familial segregation studies. Conclusions: Our findings provide novel insights into the genetic landscape of breast cancer in southern Tunisia, highlighting the clinical relevance of BRCA1/2 mutations and the contribution of other susceptibility genes. These results support the personalized management of breast cancer patients and the implementation of expanded multigene panel testing in routine clinical practice to improve genetic counseling.